LENGTH-WEIGHT RELATIONSHIP OF INDIAN MACKERELS CAUGHT OFF MANGALORE, GANGOLLI AND KARWAR BY PURSE SEINERS - Udupa, K S; Bhat, C H Krishna (Indian Journal of Fisheries, 2011)
Length-weight relationships of Indian mackerel derived for the three centres were compared for their homogeneity using the analysis of covariance technique. Comparison of condition factors with those of earlier studies showed that there is not much of a difference in the allometric growth of mackerels